Solutions to Enhance the Operational Efficiency of the Reception Department at Golden Line Hotel - Tran, Thi Anh Quyen (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management